Cross-validation of the RT-QuIC assay for the antemortem detection of chronic wasting disease in elk. Issue 1 (1st January 2020) - Haley, N.J.; Donner, R.; Henderson, D.M.; Tennant, J.; Hoover, E.A.; Manca, M.; Caughey, B.; Kondru, N.; Manne, S.; Kanthasamay, A.; Hannaoui, S.; Chang, S.C.; et al.
ABSTRACT: Chronic wasting disease is a progressively fatal, horizontally transmissible prion disease affecting several members of the cervid species. Conventional diagnosis relies on ELISA or IHC evaluation using tissues collected post-mortem; however, recent research has focused on newly developed amplification techniques using samples collected antemortem. The present study sought to cross-validate the real-time quaking-induced conversion assay (RT-QuIC) evaluation of rectal biopsies collected from an elk herd with endemic CWD, assessing both binary positive/negative test results as well as relative rates of amplification between laboratories. We found that results were correlative in both categories across all laboratories performing RT-QuIC, as well as to conventional IHC performed at a national reference laboratory. A significantly higher number of positive samples were identified using RT-QuIC, with results seemingly unhindered by low follicle counts. These findings support the continued development and implementation of amplification assays in the diagnosis of prion diseases of veterinary importance, targeting not just antemortem sampling strategies, but post-mortem testing approaches as well.